2015
DOI: 10.18632/oncotarget.2761
|View full text |Cite
|
Sign up to set email alerts
|

A serum microRNA signature associated with complete remission and progression after autologous stem-cell transplantation in patients with multiple myeloma

Abstract: We have examined serum microRNA expression in multiple myeloma (MM) patients at diagnosis and at complete response (CR) after autologous stem-cell transplantation (ASCT), in patients with stable monoclonal gammopathy of undetermined significance, and in healthy controls. MicroRNAs were first profiled using TaqMan Human MicroRNA Arrays. Differentially expressed microRNAs were then validated by individual TaqMan MicroRNA assays and correlated with CR and progression-free survival (PFS) after ASCT. Supervised ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 45 publications
5
40
0
Order By: Relevance
“…Similar results have been observed when studying serum expression of microRNAs in other tumors, including multiple myeloma, where several miRNAs were underexpressed in serum at diagnosis but increased at CR, and lower levels in serum were associated with shorter progression-free survival [44]. In cHL, only one previous study has examined microRNAs in plasma samples, and the authors identified several microRNAs, including miR-494 and miR-1973, whose levels were upregulated at diagnosis and decreased at CR [8].…”
Section: Discussionsupporting
confidence: 78%
“…Similar results have been observed when studying serum expression of microRNAs in other tumors, including multiple myeloma, where several miRNAs were underexpressed in serum at diagnosis but increased at CR, and lower levels in serum were associated with shorter progression-free survival [44]. In cHL, only one previous study has examined microRNAs in plasma samples, and the authors identified several microRNAs, including miR-494 and miR-1973, whose levels were upregulated at diagnosis and decreased at CR [8].…”
Section: Discussionsupporting
confidence: 78%
“…A decreased level of miR-331 is a marker for shorter progression-free survival in MM [25]. Moreover, downregulation of miR-331-5p and -27a was associated with chemotherapy resistance and relapse in leukaemia [26].…”
Section: Discussionmentioning
confidence: 99%
“…5 Biological implications of miR-26a, miR-29c and miR-193a have not been studied in MM, but these miRNAs were also suggested as tumor suppressors in hematologic malignancies. For example, miR-193a represses the expression of KIT and its restoration reduces the mRNA and protein levels of KIT in acute myeloid leukemia (AML).…”
Section: A B Cmentioning
confidence: 99%
“…First, some well-known prognostic miRNA markers of MM [2][3][4][5]15 such as miR-19a were not identified. Since we focused on RRMMs with bortezomib failure and used the miRNA-array which contains just part (381 miRNAs) of the known human miRNAs, there is a possibility that some significant miRNA markers were missed.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation